Apparent ileal digestibility of Maillard reaction products in growing pigs. - Sergio Salazar-Villanea; Claire I Butré; Peter A Wierenga; Erik M A M Bruininx; Harry Gruppen; Wouter H Hendriks; Antonius F B van der Poel (PLoS ONE, 2018)
The absorption of Maillard reaction products (MRP) from dietary origin has been linked to the occurrence of chronic diseases. The aim of the present study was to determine the effects of toasting time of rapeseed meal (RSM) and the processing method of the diets (pelleting and extrusion) that included RSM on the apparent ileal digestibility (AID) of total lysine, fructosyl-lysine (FL), carboxymethyl-lysine (CML), carboxyethyl-lysine (CEL), lanthionine (LAN) and lysinoalanine (LAL) in growing pigs. The study consisted of a 2×3 factorial design with toasting time of RSM (60, 120 min) and diet processing method (mash, pelleted, extruded) as factors. Fifty growing pigs were individually fed one of the experimental diets for 4.5 consecutive days. Following euthanasia, samples of digesta were collected from the terminal 1.5 m of the small intestine. Increasing the toasting time of RSM increased the contents of FL, CML and CEL, whereas the additional effects of the diet processing methods were relatively small. Lysinoalanine and lanthionine were not detected in the diets; therefore, digestibility of these compounds could not be determined. The contents of FL, CML and CEL in the ileal chyme were positively correlated to their contents in the diets. The AID of the MRP from thermally-treated RSM were overall low and were not related to their contents in the diets. The AID of FL ranged between -8.5 and 19.1%, whilst AID of CML and CEL ranged from -0.2 to 18.3 and 3.6 to 30%, respectively. In conclusion, thermal treatments have clear effects on the contents of MRP in the diets. These compounds have relatively low digestibility in growing pigs.